Subscapularis Repair Is Unnecessary After Lateralized Reverse Shoulder Arthroplasty. Issue 3 (25th September 2018) - Roberson, Troy A.; Shanley, Ellen; Griscom, James T.; Granade, Michael; Hunt, Quinn; Adams, Kyle J.; Momaya, Amit M.; Kwapisz, Adam; Kissenberth, Michael J.; Lonergan, Keith T.; Tolan, Stefan J.; Hawkins, Richard J.; et al.
Abstract : Background: Controversy exists as to whether the subscapularis should be repaired after reverse shoulder arthroplasty. The purpose of the present study was to evaluate the utility of repairing the subscapularis after reverse shoulder arthroplasty with regard to complications, objective findings, and patient-reported outcome measures. Methods: We retrospectively reviewed the records for 99 patients who had undergone a lateralized reverse shoulder arthroplasty with (n = 58) or without (n = 41) subscapularis repair. Outcomes were compared with the Single Assessment Numeric Evaluation (SANE), Penn shoulder score (PSS), Veterans RAND (VR)-12, and American Shoulder and Elbow Surgeons (ASES) score at a minimum of 2 years of follow-up. Demographics, range of motion, and complications were also compared. A 1-way analysis of variance was performed to determine differences in performance and outcome scores, and a chi-square analysis was performed to compare the frequency of complications between groups. Results: There were no significant differences between the repair and no-repair groups in terms of SANE, PSS, ASES, or VR-12 scores. There also were no significant differences between the 2 groups in terms of postoperative ranges of forward elevation (128° versus 123°; p = 0.44) and external rotation (33° versus 29°; p = 0.29), the dislocation rate (5% versus 2%; p = 0.49), or the overall complication rate (9% versus 5%; p = 0.47). Conclusions: The results of the present study suggest that repair of the subscapularis tendon after lateralized reverse shoulder arthroplasty may not be necessary. Level of Evidence: TherapeuticLevel III . See Instructions for Authors for a complete description of levels of evidence.